Ejection Fraction and Age as Predictors of Sleep Quality after Coronary Artery Bypass Graft (CABG) Surgery - Sari Eprina Nadeak; Muhamad Adam; Liya Arista (JKG (JURNAL KEPERAWATAN GLOBAL), 2026)
Background: Coronary Artery Bypass Graft (CABG) requires a longer recovery and high risk of complication including sleep quality. This study aims to identify factors associated with sleep quality in patient post-CABG surgery. Methods: This research used cross-sectional method and consecutive sampling with 100 respondents. The questionnaires used in this study were Pittsburgh Sleep Quality Index (PSQI), International Physical Activity Questionnaire (IPAQ), and Depression Anxiety Stress Scale (DASS).  Results: Prevalence of poor sleep quality (51%) was quite high compared to good sleep quality (49%). There was a significant correlation between ejection fraction (p 0,031 OR 4,718), age (p 0,039; OR 3,309), and sleep quality of post-CABG surgery. Results of logistic regression contained 4 variables related to sleep quality: ejection fraction (p 0,017 OR 5,520), age (p 0,026 OR 3,659), beta blockers (p 0,067 OR 8,544) and diabetes mellitus (p 0,145 OR 1,918).  Conclusion: Ejection fraction and age as a predictor of sleep quality. Nurses should assess the sleep quality of post-CABG surgery by considering these four variables: ejection fraction ≤ 40%, middle age, moderate-risk beta blockers and type 2 diabetes mellitus.